2014
DOI: 10.1155/2014/408503
|View full text |Cite
|
Sign up to set email alerts
|

Auraptene in the Peels of Citrus kawachiensis (Kawachi Bankan) Ameliorates Lipopolysaccharide‐Induced Inflammation in the Mouse Brain

Abstract: Examination of the dried peel powder of Citrus kawachiensis, one of the citrus products of Ehime, Japan, showed that it contained naringin (NGIN; 44.02 ± 0.491 mg/g), narirutin (NRTN; 4.46 ± 0.0563 mg/g), auraptene (AUR; 4.07 ± 0.033 mg/g), and 3,5,6,7,8,3′,4′-heptamethoxyflavone (HMF; 0.27 ± 0.0039 mg/g). When this dried peel powder was orally preadministered at the dose of 1.2 or 2.4 g/kg/day for 7 days into lipopolysaccharide- (LPS-) injected mice, an animal model of systemic inflammation, it suppressed (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 26 publications
3
42
0
2
Order By: Relevance
“…In our previous studies [8,9], we did not obtain any information to demonstrate that AUR penetrates the brain. Therefore, the final objective of the present study was to establish whether (1) AUR passes through the blood-brain barrier (BBB) and directly exerts anti-inflammatory effects in the brain; or (2) AUR remains in peripheral tissues and indirectly exerts anti-inflammatory effects in the brain.…”
Section: Introductionmentioning
confidence: 76%
See 2 more Smart Citations
“…In our previous studies [8,9], we did not obtain any information to demonstrate that AUR penetrates the brain. Therefore, the final objective of the present study was to establish whether (1) AUR passes through the blood-brain barrier (BBB) and directly exerts anti-inflammatory effects in the brain; or (2) AUR remains in peripheral tissues and indirectly exerts anti-inflammatory effects in the brain.…”
Section: Introductionmentioning
confidence: 76%
“…We previously demonstrated that COX-2 was expressed in astrocytes in ischemic brains [8] and brains with LPS-induced inflammation [9]. Thus, the second objective of the present study was to determine whether AUR had any anti-inflammatory effects in cultured astrocytes.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…These AADs are essential for activating neutrophils and thus stimulate the formation of ROS in inflammatory tissues [51,52]. Citrus flavonoids were found to affect the activation of a number of cells involved in the immune response, including T and B lymphocytes [58]. It was reported that oral administration of Citrus flavonoids can alleviate alcoholic liver disease (ALD) through preventing excessive lipid formation, suppressing induction of inflammation in hepatocytes [53].…”
Section: Anti-inflammation Activity Of Citrus Flavonoidsmentioning
confidence: 99%
“…Moreover, tangeretin was reported to have markedly reduced LPS-stimulated phosphorylation of IκB-α and IKK-β, as well as the nuclear translocation of the p65 subunit of proinflammatory transcription factor NF-κβ [57]. Furthermore, auraptene (AUR) was reported to suppress the LPS-induced inflammation in the brain of model mice possibly through inhibiting the expression of (COX)-2 [58]. Naringenin was reported to have ameliorative effects on hyperglycemia-mediated inflammation in streptozocin (STZ) -nicotinamide induced DM in Wistar rats by decreasing the values of hematological, mRNA transcript and protein indices of inflammation [59].…”
Section: Anti-inflammation Activity Of Citrus Flavonoidsmentioning
confidence: 99%